(untitled) (Research, Society and Development, 2021)
Amyotrophic lateral sclerosis is a degenerative neuromuscular disease that affects the upper and lower motor neurons. The state of motor and functional impairment resulting from the progression of the disease exposes them to a possibly fatal risk in the case of infection by SARS-CoV-2, especially due to the severe pulmonary involvement, characteristic of the advancement of the degenerative pathology in question. In this review, we list the main associative mechanisms between the disease and COVID-19, highlighting, mainly, the neuroinvasive viral aspects. The study is a qualitative descriptive research, carried out through a narrative review of the literature. The literature on the new coronavirus has demonstrated the viral neuroinvasion and neurotropic capacity of SARS-CoV-2. Currently, the evidence proves that infection is not restricted to the respiratory tract, which is the primary site of the infection. Based on the findings, it is proposed that there are three viable scenarios on the impact of SARS-CoV-2 and neuroinvasion: (1) direct induction of neurological changes; (2) worsening of previously installed neurological conditions; and (3) increased susceptibility or deterioration of damage caused by other injuries, in this case, considering ALS patients. It is concluded that there is a possibility of a latent period of SARS-CoV-2 in the CNS. Thus, it is crucial to observe subsequent neurological symptoms in the individual, resulting from viral reactivation, resulting in continuous progression of the neuroinflammatory processes associated with ALS. The neuroinvasive and neurotropic capacities of the virus must also be observed in the long term to elucidate whether neurodegenerative diseases, such as ALS, confer direct vulnerability to COVID-19.